Deep eutectic solvent pretreatment of water hyacinth for improved holocellulosic saccharification and fermentative co-production of xylitol and lipids using Rhodosporidium toruloides NCIM 3547 - Umai, Ramachandran Devasena; Jacob, Samuel; Kumar, Vinod (MDPI, 2022)
In this study, delignification of water hyacinth (WH) using a mild ionic liquid-like chemical deep eutectic solvent (DES) synthesized using choline chloride and urea was conducted and the process parameters were optimized by Box–Behnken design (BBD)-based response surface methodology (RSM). From the results, a delignification of 64.32 ± 4.08% (w/w) was obtained under 1:12.5 (biomass:DES ratio), 4.63 h (time) and 87 °C (temperature). Further, a dilute sulphuric acid (2%, v/v) hydrolysis was carried out to destabilize the hemicellulose that resulted in 23.7 ± 0.50 g/L of xylose. Fermentation of the obtained xylose was carried out using a red oleaginous yeast, Rhodosporidium toruloides NCIM 3547, with free and Ca2+-alginate-immobilized cells for xylitol production under microaerophilic conditions and obtained yields of 4.73 ± 0.40 g/L (168 h) and 9.18 ± 0.10 g/L (packed bed reactor with a retention time of 18 h), respectively. Further, when the same fermentation was performed under aerobic conditions about 40.93 ± 0.73% lipid accumulation was observed with free cells. For saccharification, Aspergillus-niger-derived cellulase was used and this resulted in a yield of 27.45 ± 0.04 g/L of glucose. The glucose-enriched hydrolysate was supplemented for fermentation under nitrogen starved conditions from which 46.81 ± 2.60% (w/w) lipid content was obtained.
Keywords: water hyacinth; deep eutectic solvent; delignification; xylose; xylitol; lipids